PEMBELAJARAN IPA BERBASIS GUIDED INQUIRY UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MURID SMP - Nadya Nurlayli Hasanah; Erman Erman (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
This study aims to describe the improvement of critical thinking skills of junior high school students after guided inquiry-based science learning, describe the implementation of guided inquiry-based science learning processes in improving critical thinking skills, and describe the responses of junior high school students after participating in guided inquiry-based science learning. The type of research used is pre-experimental with a one group pretest-posttest design. The study was conducted in the even semester of the 2025/2026 academic year with a sample of 33 eighth-grade students at a junior high school in Genteng District, Surabaya City. Data collection techniques include tests, observations, and response questionnaires. Test results were analyzed using normality tests, paired sample t-tests, and n-gain calculations. The results of the paired sample t-test showed a Sig. (2-tailed) value <0.001, which means there is a significant difference between the pretest and posttest scores. The n-gain value of 0.72 is included in the high category. The implementation of learning in the first and second meetings obtained a mode of 4 with a very well implemented category. Student responses to guided inquiry-based science learning showed very positive results, with an average percentage of 89.98%, with the criterion of strongly agreeing. Based on these results, it can be concluded that guided inquiry-based science learning can improve the critical thinking skills of junior high school students.